ملامح عامة عن سياسة الخصخصة بين الإيجابية والسلبية: دراسة تطبيقية دولة السودان للفترة من ١٩٩٨م - ٢٠٠٥ م - د. صلاح محمد ابراهيم أحمد, (White Nile Journal for Studies and Research, 2015)
This research aims at identifying privatization policy in the light of world awareness particularly in developing in countries which face new challenges created by new world systems. Nowadays most countries purse new strategies for economic growth through implementing comprehensive measures to strength and mobilize the productive resources. Also they adopt liberalization of economy market mechanism strengthening the structure of budget, improving the ability to attract internal and external fund. encouraging investment and reforming legal system. The most important results are Sudan strongly has adopted privatization policy concerning economical activities approximately beside A companies have been privatized and production has been increased in quantity and quality. Those who found chances to work are double the number of these who left the work. The government stopped funding failure companies and reduced the deficit of the budget. Expanding the activities of the private sector. The important recommendations are: Raising the awareness of the Sudan citizens concerning the privatization policy